Pengaruh Model Discovery Learning terhadap Keterampilan Menulis Teks Laporan Hasil Observasi - Putri, Agustia Maharani; Atmazaki, Atmazaki (Lembaga Yasin AlSys, 2023)
The fundamental background of this study is that researchers want to pilot the use of discovery learning models, whether discovery learning models can be an effective alternative in closing the weaknesses of models that have been used before or vice versa. This study was conducted with the aim of determining the effect of the discovery learning model on the text writing skills of observation reports of grade VII students of SMP Negeri 24 Padang. Thisstudy researchers used experimental research methods to reveal cause-and-effect relationships with hypotheses. This research uses a research design or design in the form of one group pretest-posttest design. The population in this study is grade VII students of SMP Negeri 24 Padang who are registered for 2022-2023 which amounts to 254. Based on data analysis and previous discussions, several results can be presented. First, the skill of writing the text of the observation report of grade VII students of SMP Negeri 24 Padang before using the discovery learning model obtained a number of 66.38 with a classification of